The Impact of Service Quality, Price, and Trust on Customer Loyalty - wati, Elfira; Artina, Nyimas (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of service quality, price, perceived value, and trust on customer loyalty at Caffe Little Palembang. A quantitative approach was employed in this study, utilizing survey and interview methods through the distribution of questionnaires. The sampling technique used was purposive sampling, with a total of 396 respondents. Data were analyzed using multiple linear regression with the help of SPSS version 26. The results indicate that both partially and simultaneously, service quality, price, perceived value, and trust have a positive and significant effect on customer loyalty. The coefficient of determination (R²) value of 0.853 shows that 85.3% of the variation in customer loyalty can be explained by these four variables, while the remaining 14.7% is influenced by other factors not examined in this study. In conclusion, enhancing customer loyalty can be achieved by maintaining high service quality, implementing appropriate pricing strategies, offering added value, and consistently building trust. This study provides valuable insights into the combined impact of service quality, price, perceived value, and trust on customer loyalty in the context of a local café business in Palembang. Unlike previous studies that often focused on large-scale or international brands, this research highlights the importance of these factors in small and medium-sized enterprises (SMEs), particularly in the food and beverage sector. The findings offer practical implications for business owners seeking to improve customer retention through targeted strategies based on customer perceptions and trust-building efforts.